2011
DOI: 10.1007/s10856-011-4453-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphate-based glass fibre surface properties on thermally produced poly(lactic acid) matrix composites

Abstract: Incorporation of soluble bioactive glass fibres into biodegradable polymers is an interesting approach for bone repair and regeneration. However, the glass composition and its surface properties significantly affect the nature of the fibre-matrix interface and composite properties. Herein, the effect of Si and Fe on the surface properties of calcium containing phosphate based glasses (PGs) in the system (50P(2)O(5)-40CaO-(10-x)SiO(2)-xFe(2)O(3), where x = 0, 5 and 10 mol.%) were investigated. Contact angle mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…They studied the change in fibre solubility and surface hydrophilicity produced by the incorporation of SiO 2 due to its ability to disrupt the PG network. As seen with previous studies, the incorporation of 10 mm length, ≈10-20 μm diameter PGFs in a PLA or PCL matrix (≈0.18 V f ) resulted in an increase to the flexural strength and elastic modulus [33,68]. Comparisons of degradation in distilled water or PBS revealed that the 10 mol% Fe 2 O 3 composites showed a lower weight loss and greater retention of mechanical properties compared to the 5 mol% SiO 2 samples.…”
Section: Composite Investigationssupporting
confidence: 82%
See 1 more Smart Citation
“…They studied the change in fibre solubility and surface hydrophilicity produced by the incorporation of SiO 2 due to its ability to disrupt the PG network. As seen with previous studies, the incorporation of 10 mm length, ≈10-20 μm diameter PGFs in a PLA or PCL matrix (≈0.18 V f ) resulted in an increase to the flexural strength and elastic modulus [33,68]. Comparisons of degradation in distilled water or PBS revealed that the 10 mol% Fe 2 O 3 composites showed a lower weight loss and greater retention of mechanical properties compared to the 5 mol% SiO 2 samples.…”
Section: Composite Investigationssupporting
confidence: 82%
“…For PGF reinforced degradable polymer composites, typically fibre diameters of ≈20 μm have been used [31][32][33][34][35] similar to the 10-20 μm fibre diameters found in commercially available fibre reinforced composites. This is due to the high aspect ratio (i.e.…”
Section: Phosphate Glass Fibres 21 Fibre Manufacturementioning
confidence: 99%
“…Biocompatibility of both PCL (approved by FDA) and of phosphate based glass fibre (PGF) has been well investigated and both are known to be bioresorbable, which makes these materials favourable candidates for bone repair applications [3][4][5][6]. Most recently, PGF has been used as reinforcement for developing fully bioresorbable polymer composites [2,7,8]. PGFs are able to dissolve completely within aqueous media and their dissolution rate can be adjusted easily by altering the glass composition [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of polymer composites, such as PGF/PCL, is limited by the rapid loss of their strength profiles after exposure to an aqueous physiological environment, which has been suggested to be due to loss of their interfacial properties [5]. Recently, coupling agents have been explored to enhance the interfacial properties of fibre/polymer composites [6,7]. Chitosan (CS) has a number of properties that make it a suitable candidate as an interface agent for PGF/PCL composites.…”
Section: Introductionmentioning
confidence: 99%